ANALYSIS OF DIFFERENCES IN LEAD LEVELS (PB) IN BLOOD AND BONE DENSITY BEFORE AND AFTER CONSUMPTION OF GREEN COCONUT WATER AND MILK IN WORKERS AT THE "X" PAINTING BODY - Iyou, Ismelda; Wahyuningsih , Nur Endah; Sulistiyani (International Journal of Research -GRANTHAALAYAH, 2018)
Background: Lead (Pb) becomes toxic to osteoblast cells and osteoclasts that affect the biology and deposition of bone mineral, thereby boosting the risk of osteoporosis. Green coconut water contains the highest tannins or antidotum (anti toxins), recommended for consumption for people exposed to heavy metals. While milk naturally contains essential nutrients to help control the regeneration of bone cells and strengthen bones. Method: This research is a quasi experimental research using the one group pretest and posttest design. The number of research samples are 30 people who were given treatment of green coconut water and milk as much as 250 ml alternately for 10 days Result: Before the intervention of the lead category in the blood of the respondents exceeded the threshold value of NIOSH (10 μg / dL), ie 23 people averaged 14.04 μg / dL and after intervention decreased to 7 people on average 11.88 μg / dL. The categories of osteopenia before intervention were 8 respondents averaging -0.59 and after intervention decreased ie 4 respondents average -1.90. Conclusion: There was a difference of Pb levels in blood before and after consumption of green coconut water and milk with p value = 0,001 (p value <0,05). There was a difference of bone density before and after consumption of green coconut water and milk with p value = 0,000 (p value <0,05).